The Rapid and Accurate Categorisation of Critically Ill Patients (RACE) to Identify Outcomes of Interest for Longitudinal Studies: A Feasibility Study. Issue 4 (July 2017) - Deane, A. M.; Hodgson, C. L.; Young, P.; Little, L.; Singh, V.; Poole, A.; Young, M.; Mackle, D.; Lange, K.; Williams, P.; Peake, S. L.; Chapman, M. J.; et al.
The capacity to measure the impact of an intervention on long-term functional outcomes might be improved if research methodology reflected our clinical approach, which is to individualise goals of care to what is achievable for each patient. The objective of this multicentre inception cohort study was to evaluate the feasibility of rapidly and accurately categorising patients, who were eligible for simulated enrolment into a clinical trial, into unique categories based on premorbid function. Once a patient met eligibility criteria a rapid 'baseline assessment' was conducted to categorise patients into one of eight specified groups. A subsequent 'gold standard' assessment was made by an independent blinded assessor once patients had recovered sufficiently to allow such an assessment to occur. Accuracy was predefined as agreement in >80% of assessments. One hundred and twenty-two patients received a baseline assessment and 104 (85%) were categorised to a unique category. One hundred and six patients survived to have a gold standard assessment performed, with 100 (94%) assigned to a unique category. Ninety-two patients had both a baseline and gold standard assessment, and these agreed in 65 (71%) patients. It was not feasible to rapidly and accurately categorise patients according to premorbid function.